Fermentative Production of Citric acid by Aspergillus niger strains Using Sugarcane Bagasse as the substrate (International Journal of Food and Nutritional Sciences, 2022)
An essential organic acid, citric acid is employed in many pharmaceutical and other commercial food items. A rise in the demand for citric acid has prompted researchers worldwide to look for high yielding microorganism strains and less expensive fermentation substrate. The current work examines the isolation, screening, and synthesis of citric acid by A. niger (MTCC 281) and local (isolates), with sugar cane bagasse serving as the substrate. The yield was compared after two distinct inoculums were used in the fermentation process: set 1 had spore suspension as the inoculum, while set 2 contained the entire mycelium. The fermenting process took six days to complete. Right after autoclaving, following the addition samples of the inoculums were taken, and the levels of sugar and citric acid were first determined. Every 48 hours, samples were taken and analysed to estimate the amount of residual sugar and citric acid produced. Citric acid production was calculated spectrophotometrically using the pyridine acetic anhydride method, and residual sugar was calculated using the 3, 5 DNS method. The MTCC culture with intact mycelium had a higher yield than the spore suspension and was determined to be more suited.